A triple blind, placebo controlled, randomised controlled trial of betahistine dihydrochloride in the treatment of primary tinnitus - Castilho, Gustavo Leão [UNESP]; Dias, Norimar Hernanes [UNESP]; Martins, Regina Helena Garcia [UNESP] (Wiley, 2023)
Objectives: To evaluate the effectiveness of betahistine in the treatment of primary tinnitus. Design: To evaluate the effectiveness of betahistine in the treatment of primary tinnitus. Setting: Universidade estadual Paulista Julio de Mesquita Filho, Botucatu Medical School, São paulo, Brazil. Participants: Adult patients with primary tinnitus who had not undergone treatment for tinnitus in the last 6 months were included. Patients with profound sensorineural deafness, hearing aid users and patients with metabolic, neurological, psychiatric or decompensated cardiovascular diseases were excluded. Study groups: in the betahistine group, patients received betahistine 24 mg every 12 h for 90 days; in the control group, patients received placebo tablets every 12 h for 90 days. Mean Outcome Measures: Primary outcome measure: Tinnitus Handicap Inventory (THI). Secondary outcome measures: Clinical Global Impression Improvement (CGI-I) and a question of ‘Yes’ or ‘No’ to participants about their perception of improvement in symptoms. Results: Of 284 participants initially identified, 62 were randomised (betahistine group n = 31; control group n = 31). Median age (IQR) 54 (48–60) years, with a balanced number of men and women. There was no difference in THI outcome between the study groups (median difference, −2 points; 95% CI, −8 to 6 points); the THI after the intervention was a median (IQR) 4 (−4 to 14) lower points in the betahistine group, and a median (IQR) 2 (−6 to 10) in the control group. There was no statistical difference in secondary outcome measures. Adverse events were mild and there was no statistical difference between groups. Conclusions: Betahistine dihydrochloride was ineffective in the treatment of primary tinnitus in adults.
Keywords: betahistine dihydrochloride; clinical trial; tinnitus; treatment